Mission impossible? Motivating hospitality managers in Cyprus - Constanti, Panikkos; Zopiatis, Anastasios (My University, 2007)
The hospitality industry is renowned for its ‘pressure cooker’ environment of long hours and high turnover, particularly among front line staff. However, there have been relatively few investigations into the life of supervisors and managers in the industry. Utilizing surveys, the study set out to identify the motivational factors that directly impact on this category of employees. Factors such as appreciation, interesting job, good working conditions, career opportunities and loyalty by the organization were ranked as the top five motivators. The findings challenge a long-standing perception of Cypriot hospitality stakeholders who suggest that money is the major motivator. It was also found that the motivators are the same irrespective of gender, and age. However, these are likely to change as one moves within the management hierarchy. The findings are primarily intended for companies within a Cyprus framework, and therefore the research is focused on the needs for these organizations. However, there are likely to be parallels for hospitality organizations outside Cyprus.
Keywords: Motivation; Motivational factors; Hospitality managers; Motivational working environment; Open access publishing